Arabic Proverbs as a Pedagogical Tool to Enhance Arabic Speaking Skills among University Students - Agil, Abdurrahman Ahmad; Mahmudah, Menik (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
The teaching of Arabic speaking skills (Mahārah Kalām) often faces persistent challenges, particularly among learners in non-Arabic speaking environments who struggle to achieve fluency despite adequate grammatical knowledge. To address this gap, this study investigates the pedagogical potential of Arabic proverbs (al-amthāl al-‘arabiyyah) as culturally grounded tools for enhancing oral proficiency. Using a qualitative research design, the study was conducted with 30 undergraduate students of Arabic Language Education at Darullughah Wadda’wah International Islamic University. Data were collected through classroom observations, in-depth interviews, and document analysis, and analyzed using Miles and Huberman’s interactive model. The findings reveal three major outcomes: increased fluency and confidence through access to ready-made linguistic chunks, heightened cultural awareness and rhetorical sensitivity by engaging with moral and social values embedded in proverbs, and challenges in figurative comprehension and pragmatic application, which necessitate explicit instructional scaffolding. Despite these challenges, proverb-based pedagogy was shown to foster spontaneous communication, intercultural competence, and learner motivation. The study concludes that Arabic proverbs represent an effective pedagogical resource bridging linguistic knowledge and authentic oral expression, offering practical implications for Arabic language educators to integrate proverbs systematically into speaking activities and assessments.